Salt and Heat Stress Trigger Morpho-Physiological Changes, Antioxidant Enzyme and Secondary Metabolites Gene Expression in Rice (Oryza sativa L.) - Ubaidillah, Mohammad; Rozzita, Noor; Mufadilah, Mitha Aprilia; Thamrin , Nurhaliza; Puspito, Agung Nugroho; Kim, Kyung Min (HAYATI Journal of Biosciences, 2024)
Climate change significantly increases salt and heat stress in rice plants. This condition causes plants to activate antioxidant enzymes and produce secondary metabolites. This study aimed to determine the morpho-physiological changes and gene expression profiles of antioxidant enzymes and secondary metabolites. This study used a completely randomized design factorial. The first factor was local rice varieties (IR64, Silaun, and Cigeulis), and the second factor was stress treatments (control, NaCl 150 mM, 40°C, and NaCl 150 mM + 40°C). The results showed that multiple stress significantly affected the plant height, stem length, stem diameter, leaf area, root length, total main root, plant biomass, necrotic length, chlorophyll content, relative water content, and plant ROS production. Multiple stress could up-regulate the gene expression of antioxidant enzymes (Mn-SOD, Cu/Zn SOD, Cytosolic APX, OsAPX1, CAT, OsCATA, and GPOD) in rice after stress combination treatments and increase the secondary metabolites gene expression (P5CS and GABA-T) in all rice varieties. Still, the OsNOMT gene was only active in the Cigeulis variety.